∑n=1k(−1)n+1(kn)∑1≤i≤j≤n1ij=1k2 \large \displaystyle\sum _{ n=1 }^{ k }{ { (-1) }^{ n+1 } } \dbinom{ k }{ n }\displaystyle\sum _{ 1\le i\le j\le n }{ \dfrac { 1 }{ ij } } =\dfrac { 1 }{ { k }^{ 2 } } n=1∑k(−1)n+1(nk)1≤i≤j≤n∑ij1=k21
Prove the equation above.
This is a part of the set Formidable Series and Integrals
Note by Hamza A 5 years, 3 months ago
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
_italics_
**bold**
__bold__
- bulleted- list
1. numbered2. list
paragraph 1paragraph 2
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
This is a quote
# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"
\(
\)
\[
\]
2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
For this solution, take (nk)=0\displaystyle \binom{n}{k} = 0(kn)=0 if k>nk>nk>n.
Lemma 1: ∑k=1n∑i=1k1ik=∑i=1n(−1)i+1i2(ni) \displaystyle \sum _{k=1}^{n} \sum _{i=1}^{k} \frac {1}{ik} = \sum_{i=1}^n\frac{\left(-1\right)^{i+1}}{i^2}\binom{n}{i} k=1∑ni=1∑kik1=i=1∑ni2(−1)i+1(in)
Proof: ∑k=1n∑i=1k1ik=∑k=1n1k∑i=1k1i=∫01∑k=1n1k∑i=1kxi−1dx=∫011x−1∑k=1n1k(xk−1)dx=∫011u∑k=1n1k(1−(1−u)k)du=∫011u∑k=1n1k(1−∑i=0k(−1)i(ki)ui)du=∑k=1n1k∫01(∑i=1k(−1)i+1(ki)ui−1)du=∑k=1n1k∑i=1k(−1)i+1i(ki)=∑k=1n1k∑i=1n(−1)i+1i(ki)=∑i=1n(−1)i+1i∑k=1n1k(ki)=∑i=1n(−1)i+1i2∑k=1n(k−1i−1)=∑i=1n(−1)i+1i2∑k=in(ki)−(k−1i)=∑i=1n(−1)i+1i2(ni) \begin{aligned} \sum_{k=1}^n\sum_{i=1}^k\frac{1}{ik} &= \sum_{k=1}^n\frac{1}{k}\sum_{i=1}^k\frac{1}{i} \\ &= \int_0^1\sum_{k=1}^n\frac{1}{k}\sum_{i=1}^kx^{i-1}dx \\ &= \int_0^1\frac{1}{x-1}\sum_{k=1}^n\frac{1}{k}\left(x^k-1\right)dx \\ &= \int_0^1\frac{1}{u}\sum_{k=1}^n\frac{1}{k}\left(1-\left(1-u\right)^k\right)du \\ &= \int_0^1\frac{1}{u}\sum_{k=1}^n\frac{1}{k}\left(1-\sum_{i=0}^k\left(-1\right)^i\binom{k}{i}u^i\right)du \\ &= \sum_{k=1}^n\frac{1}{k}\int_0^1\left(\sum_{i=1}^k\left(-1\right)^{i+1}\binom{k}{i}u^{i-1}\right)du \\ &= \sum_{k=1}^n\frac{1}{k}\sum_{i=1}^k\frac{\left(-1\right)^{i+1}}{i}\binom{k}{i} \\ &= \sum_{k=1}^n\frac{1}{k}\sum_{i=1}^n\frac{\left(-1\right)^{i+1}}{i}\binom{k}{i} \\ &= \sum_{i=1}^n\frac{(-1)^{i+1}}{i}\sum_{k=1}^n\frac{1}{k}\binom{k}{i} \\ &= \sum_{i=1}^n\frac{\left(-1\right)^{i+1}}{i^2}\sum_{k=1}^n\binom{k-1}{i-1}\\ &= \sum_{i=1}^n\frac{\left(-1\right)^{i+1}}{i^2}\sum_{k=i}^n\binom{k}{i}-\binom{k-1}{i} \\ &= \sum_{i=1}^n\frac{\left(-1\right)^{i+1}}{i^2}\binom{n}{i} \end{aligned} k=1∑ni=1∑kik1=k=1∑nk1i=1∑ki1=∫01k=1∑nk1i=1∑kxi−1dx=∫01x−11k=1∑nk1(xk−1)dx=∫01u1k=1∑nk1(1−(1−u)k)du=∫01u1k=1∑nk1(1−i=0∑k(−1)i(ik)ui)du=k=1∑nk1∫01(i=1∑k(−1)i+1(ik)ui−1)du=k=1∑nk1i=1∑ki(−1)i+1(ik)=k=1∑nk1i=1∑ni(−1)i+1(ik)=i=1∑ni(−1)i+1k=1∑nk1(ik)=i=1∑ni2(−1)i+1k=1∑n(i−1k−1)=i=1∑ni2(−1)i+1k=i∑n(ik)−(ik−1)=i=1∑ni2(−1)i+1(in)
So: \begin{aligned} \sum_{n=1}^k(-1)^{n+1}\binom{k}{n}\sum_{1\le i\le j\le n}\frac{1}{ij} &= \sum_{n=1}^k(-1)^{n+1}\binom{k}{n}\sum_{i=1}^n\frac{(-1)^{i+1}}{i^2}\binom{n}{i} \\ &= \sum_{n=1}^k(-1)^{n+1}\binom{k}{n}\sum_{i=1}^k\frac{(-1)^{i+1}}{i^2}\binom{n}{i} \\ &= \sum_{i=1}^k\frac{(-1)^{i}}{i^2}\sum_{n=1}^k(-1)^{n}\binom{k}{n}\binom{n}{i} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\sum_{n=0}^{k-1}(-1)^{k-n}\binom{k}{k-n}\binom{k-n}{i} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\sum_{n=0}^{k-1}(-1)^{k-n}\binom{k}{k-n}\binom{k-n}{i} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\sum_{n=0}^{k-1}(-1)^{k-n}\binom{k}{i}\binom{k-i}{n} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\binom{k}{i}\sum_{n=0}^{k-1}(-1)^{k-n}\binom{k-i}{n} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\binom{k}{i}\sum_{n=0}^{k-i}(-1)^{k-n}\binom{k-i}{n} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\binom{k}{i}\begin{Bmatrix} 0 & \text{ if } i<k \\ (-1)^k & \text{ if }i=k \end{Bmatrix} \\ &= \left \frac{(-1)^{i}}{i^{2}}\binom{k}{i}\right|_{i=k}(-1) ^{k} \\ &= \frac{1}{k^2} \end{aligned} If the above LaTeX has problems rendering, refer to the bottom image:
Note that what I did in this proof is essentially a binomial transform.
Problem Loading...
Note Loading...
Set Loading...
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
For this solution, take (kn)=0 if k>n.
Lemma 1: k=1∑ni=1∑kik1=i=1∑ni2(−1)i+1(in)
Proof: k=1∑ni=1∑kik1=k=1∑nk1i=1∑ki1=∫01k=1∑nk1i=1∑kxi−1dx=∫01x−11k=1∑nk1(xk−1)dx=∫01u1k=1∑nk1(1−(1−u)k)du=∫01u1k=1∑nk1(1−i=0∑k(−1)i(ik)ui)du=k=1∑nk1∫01(i=1∑k(−1)i+1(ik)ui−1)du=k=1∑nk1i=1∑ki(−1)i+1(ik)=k=1∑nk1i=1∑ni(−1)i+1(ik)=i=1∑ni(−1)i+1k=1∑nk1(ik)=i=1∑ni2(−1)i+1k=1∑n(i−1k−1)=i=1∑ni2(−1)i+1k=i∑n(ik)−(ik−1)=i=1∑ni2(−1)i+1(in)
So: \begin{aligned} \sum_{n=1}^k(-1)^{n+1}\binom{k}{n}\sum_{1\le i\le j\le n}\frac{1}{ij} &= \sum_{n=1}^k(-1)^{n+1}\binom{k}{n}\sum_{i=1}^n\frac{(-1)^{i+1}}{i^2}\binom{n}{i} \\ &= \sum_{n=1}^k(-1)^{n+1}\binom{k}{n}\sum_{i=1}^k\frac{(-1)^{i+1}}{i^2}\binom{n}{i} \\ &= \sum_{i=1}^k\frac{(-1)^{i}}{i^2}\sum_{n=1}^k(-1)^{n}\binom{k}{n}\binom{n}{i} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\sum_{n=0}^{k-1}(-1)^{k-n}\binom{k}{k-n}\binom{k-n}{i} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\sum_{n=0}^{k-1}(-1)^{k-n}\binom{k}{k-n}\binom{k-n}{i} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\sum_{n=0}^{k-1}(-1)^{k-n}\binom{k}{i}\binom{k-i}{n} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\binom{k}{i}\sum_{n=0}^{k-1}(-1)^{k-n}\binom{k-i}{n} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\binom{k}{i}\sum_{n=0}^{k-i}(-1)^{k-n}\binom{k-i}{n} \\ &= \sum_{i=1}^k\frac{(-1)^i}{i^2}\binom{k}{i}\begin{Bmatrix} 0 & \text{ if } i<k \\ (-1)^k & \text{ if }i=k \end{Bmatrix} \\ &= \left \frac{(-1)^{i}}{i^{2}}\binom{k}{i}\right|_{i=k}(-1) ^{k} \\ &= \frac{1}{k^2} \end{aligned} If the above LaTeX has problems rendering, refer to the bottom image:
Note that what I did in this proof is essentially a binomial transform.